X-Ray Diffraction - Warren, B E (New York : Dover Publishers, 1990)
Basic diffraction theory has numerous important applications in solid-state physics and physical metallurgy, and this graduate-level text is the ideal introduction to the fundamentals of the discipline. Development is rigorous (throughout the book, the treatment is carried far enough to relate to experimentally observable quantities) and stress is placed on modern applications to nonstructural problems such as temperature vibration effects, order-disorder phenomena, crystal imperfections, the structure of amorphous materials, and the diffraction of x-rays in perfect crystals. Carefully selected problems have been included at the end of each chapter to help the student test his or her grasp of the material. Professor Warren, a recognized authority on the use of x-rays to probe the structure of matter, is Professor Emeritus of Physics, Massachusetts Institute of Technology.
Includes bibliographical references; Index 377-381p.
Keywords: Physics; X-Ray diffraction; General Science